2015
DOI: 10.1093/mnras/stv2105
|View full text |Cite
|
Sign up to set email alerts
|

Fast radio bursts: the observational case for a Galactic origin

Abstract: There are by now ten published detections of fast radio bursts (FRBs)-single bright GHz-band millisecond pulses of unknown origin. Proposed explanations cover a broad range from exotic processes at cosmological distances to atmospheric and terrestrial sources. Loeb, Maoz, and Shvartzvald have previously suggested that FRB sources could be nearby flare stars, and pointed out the presence of a W-UMa-type contact binary within the beam of one out of three FRB fields that they examined. To further test the flare-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 61 publications
1
35
0
Order By: Relevance
“…They are very short (∼ 1 − 10 ms) and bright (∼ 0.1 − 1 Jy) sporadic events observed in the ∼ 1 GHz bands showing a large dispersion measure (DM), DM ∼ 500 − 1000 pc cm −3 . If the dispersion originates mainly from the intergalactic propagation (Ioka 2003;Inoue 2004), the sources can be at cosmological distance up to z ∼ 1 (but see, e.g., Loeb, Shvartzvald & Maoz 2014;Maoz et al 2015), and a high brightness temperature requires a coherent emission mechanism (e.g., Lorimer et al 2007;Lyubarsky 2008;Thornton et al 2013;Katz 2014). Interestingly, despite being relatively common (∼ 10 % of core-collapse supernovae; Thornton et al 2013;Keane & Petroff 2015;Law et al 2015), the origin of FRBs is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…They are very short (∼ 1 − 10 ms) and bright (∼ 0.1 − 1 Jy) sporadic events observed in the ∼ 1 GHz bands showing a large dispersion measure (DM), DM ∼ 500 − 1000 pc cm −3 . If the dispersion originates mainly from the intergalactic propagation (Ioka 2003;Inoue 2004), the sources can be at cosmological distance up to z ∼ 1 (but see, e.g., Loeb, Shvartzvald & Maoz 2014;Maoz et al 2015), and a high brightness temperature requires a coherent emission mechanism (e.g., Lorimer et al 2007;Lyubarsky 2008;Thornton et al 2013;Katz 2014). Interestingly, despite being relatively common (∼ 10 % of core-collapse supernovae; Thornton et al 2013;Keane & Petroff 2015;Law et al 2015), the origin of FRBs is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nearby Galactic (D ∼ < 1 kpc) flare stars have been proposed as repeating FRB sources (Loeb et al 2014). FRB 131104, however, has no apparent variable stars within its sky localization (Maoz et al 2015), and has not been observed to repeat (Ravi et al 2015). A local extragalactic origin, as from giant pulses of a pulsar in the Carina dwarf spheroidal galaxy or Magellanic stream (Ravi et al 2015), is also excluded, as pulsar giant pulses are not accompanied by gamma-ray emission.…”
Section: Discussionmentioning
confidence: 99%
“…2) does not reveal any prominent Local Group or low-redshift galaxies, nor bright active galaxies, although as noted by Ravi et al (2015), the field is near the projected tidal limit of the Carina dwarf spheroidal galaxy (D ≈ 100 kpc) and a projected tidal stream of the Large Magellanic Cloud (D ≈ 50 kpc). The absence of known or candidate flare stars has been noted by Maoz et al (2015).…”
Section: Counterpart Propertiesmentioning
confidence: 99%
“…All detected FRBs to date possess high DMs, which yield burst widths of ∼ 1 − 10 ms [15][16][17][18][19][20][21][22][23][24]. These values of the DM are several times larger than the expected contribution from free electrons within the Milky Way [25,26], suggesting their origin is extragalactic (some authors, however, prefer a Galactic origin [27,28]). Proposed sources of extragalactic FRBs include merging neutron stars [29] or white dwarfs [30], as well as bursts from pulsars [31].…”
mentioning
confidence: 99%